1989
DOI: 10.1007/bf00679777
|View full text |Cite
|
Sign up to set email alerts
|

Human scalp hair as evidence of individual dosage history of haloperidol: method and retrospective study

Abstract: Hair samples and morning pre-dose plasma were collected from 40 patients who had received fixed daily doses of haloperidol for more than four months and whose compliance was good. After washing, 1 to 2 cm-long portions nearest to the roots of 2 to 3 strands of hair were completely dissolved in 2.5N NaOH. Haloperidol in that sample or alkalinised plasma was extracted and measured by RIA. Haloperidol concentrations in hair correlated well both with the trough concentration in plasma at steady-state (r = 0.772, n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
28
0

Year Published

1990
1990
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 72 publications
(28 citation statements)
references
References 18 publications
0
28
0
Order By: Relevance
“…In addition to the use of hair assays for the identification of illicit psychoactive drug use, it has also been applied to a variety of medicinals, such as antibiotics, antipsychotics, and anti-epileptics (Uematsu et al, 1989;Mieczkowski, 2000;Mieczkowski et al, 2001). Also, it has become a frequently used method for assessing compliance to drug abstinence requirements in such programs as driver's license restoration (Mangin, 1995) various drug abuse disciplinary actions (Knight, 1998), and testing of sensitive employment positions (Cook, 1997).…”
Section: Introductionmentioning
confidence: 98%
“…In addition to the use of hair assays for the identification of illicit psychoactive drug use, it has also been applied to a variety of medicinals, such as antibiotics, antipsychotics, and anti-epileptics (Uematsu et al, 1989;Mieczkowski, 2000;Mieczkowski et al, 2001). Also, it has become a frequently used method for assessing compliance to drug abstinence requirements in such programs as driver's license restoration (Mangin, 1995) various drug abuse disciplinary actions (Knight, 1998), and testing of sensitive employment positions (Cook, 1997).…”
Section: Introductionmentioning
confidence: 98%
“…Several therapeutic, but potentially toxic, drugs such as antidepressants, antipsychotics, and tranquillizers have been determined in hair, for tricyclic and tetracyclic antidepressant readers can refer to the papers by Couper et al (1995a, b) and for haloperidol to the papers by Uematsu et al (1989) and Matsuno et al (1990). Research on benzodiazepine analysis in hair has also been published (Toyo'oka et al 2003;Kangas 1979;Höld et al 1997).…”
Section: Advances Made In Hair Analysismentioning
confidence: 95%
“…The dilution of antiserum which exhibited 50% binding to the labelled antigen was 1:4500, showing an appropriately high affinity for haloperidol. The procedures for measuring haloperidol in hair with the radioimmunoassay are described in detail elsewhere (Uematsu et al, 1989). Cross-reactivities of haloperidol with its major metabolites have been reported to be less than 0.1% (Suzuki et al, 1980).…”
Section: Preparation Of Samplesmentioning
confidence: 99%
“…Our purpose was to correlate quantitively the content of drug and metabolite in hair with the dose and with steady-state plasma drug concentrations in order to use the analysis of hair for therapeutic drug monitoring. In a previous communication (Uematsu et al, 1989) we suggested that hair might be superior to plasma for the therapeutic drug monitoring of haloperidol because the concentration of haloperidol in hair correlated with daily dosage while the trough plasma concentration of haloperidol, which is usually employed for routine therapeutic drug monitoring, did not represent the daily dose. Again in the present study, which used a larger number of patients, the trough plasma concentration of haloperidol did not correlate significantly with daily dose, while the concentration of haloperidol and reduced haloperidol in hair did.…”
Section: Preparation Of Samplesmentioning
confidence: 99%
See 1 more Smart Citation